Bryde's whales in the North‐East Atlantic: New insights on site fidelity and connectivity between oceanic archipelagos. Issue 10 (30th July 2021) - Ferreira, Rita; Dinis, Ana; Badenas, Anja; Sambolino, Annalisa; Marrero‐Pérez, Jacobo; Crespo, Ana; Alves, Filipe
Abstract: The conservation of marine megafauna presents numerous difficulties owing to their high mobility over difficult‐to‐access oceanic areas that impairs the collection of basic, but essential, biological information. The Bryde's whale ( Balaenoptera edeni ) is one of the most elusive species of baleen whales, and although it is known to be a seasonal visitor to several archipelagos in Macaronesia (the Azores, Madeira, and Canaries), there are no studies regarding its occurrence or geographical connectivity in this area of the Atlantic. A 14‐year photographic database was used to determine short‐term (intra‐seasonal) and long‐term (inter‐annual) Bryde's whale site fidelity and to estimate individual residency times in Madeira, whereas photographic catalogues from Madeira and the Canaries were compared in order to assess large‐scale movements (i.e. on the scale of hundreds of kilometres). In Madeira, 59 individuals were identified, 27 (45.8%) of which were recaptured. Of these, 10 individuals (37.0%) presented short‐term site fidelity and 17 individuals (63.0%) presented long‐term site fidelity, with a maximum recapture interval of 12 years. Lagged identification rates showed that five individuals (SE = 2) remained in the area for 32 days (SE = 108 days) before leaving and not returning during the same year. Seven individuals were seen both in Madeira and the Canaries (catalogue comprising 51 individuals), three of which were identified multiple times in both archipelagos, with a minimum of 43 days between consecutive sightings. This information combined with the fact that this species is commonly sighted accompanied by calves and feeding in both archipelagos highlights the ecological importance of this area for Bryde's whales. This should be taken into consideration by policymakers when implementing conservation measures, where coordination of effort among countries is needed. This study also reinforces the value of using data from platforms of opportunity and of making photographic data open access.